2021
DOI: 10.1002/mame.202100466
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bio‐Based Cobalt Alginate on the Fire Safety and Mechanical Properties for Epoxy Resin

Abstract: There is a growing demand to develop epoxy resins (EP) with smoke suppression as well as satisfactory flame retardancy. Herein, bio‐based cobalt alginate is successfully fabricated and incorporated into EP to prepare EP/Cobalt Alginate composites with better fire safety performance. The addition of cobalt alginate reduces the thermal‐decomposition rate, temperature at maximum weight‐loss rate of EP, whereas obviously improves the thermal stabilities at a higher temperature range. Furthermore, the addition of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 56 publications
(41 reference statements)
0
8
0
Order By: Relevance
“…On the basis of the condensed and gaseous phase analysis, a feasible flame retardant mechanism is proposed as follows for the ZIF-based hybrid flame retardant prepared in this work. ZIF@LDH@PZS played its role in both the condensed and gaseous phases, and specifically speaking, in the condensed phase, the transition metals Ni and Co derived from LDH catalyzed char formation together with the phosphoric acid generated by PZS. , Meanwhile, the decomposition process of the LDH is endothermic, thus cooling the flame zone to mitigate the burning degree. When the metals migrated to the flame zone, some parts reacted with phosphoric acid to form metal phosphates, and other parts formed metal oxides as coverage on the surface .…”
Section: Resultsmentioning
confidence: 99%
“…On the basis of the condensed and gaseous phase analysis, a feasible flame retardant mechanism is proposed as follows for the ZIF-based hybrid flame retardant prepared in this work. ZIF@LDH@PZS played its role in both the condensed and gaseous phases, and specifically speaking, in the condensed phase, the transition metals Ni and Co derived from LDH catalyzed char formation together with the phosphoric acid generated by PZS. , Meanwhile, the decomposition process of the LDH is endothermic, thus cooling the flame zone to mitigate the burning degree. When the metals migrated to the flame zone, some parts reacted with phosphoric acid to form metal phosphates, and other parts formed metal oxides as coverage on the surface .…”
Section: Resultsmentioning
confidence: 99%
“…CO 2 and CO production are also investigated to research the toxicity of the burning products. 40 From Figure 3e,f, both CO 2 production rate (CO 2 P) and CO production rate (COP) of EP are comparatively higher, while those of FR-EPs are much lower. Besides, EP/AlPi 9.5 -Nickel Alginate 0.5 presents the lowest CO 2 P and COP, indicating the suitable nickel alginate amount can suppress the smoke release of EP/AlPi, and that the synergistic effect between AlPi and nickel alginate exists.…”
Section: Cone Calorimeter Testmentioning
confidence: 90%
“…Nabipour et al prepared a zinc-containing triazole complex for EP flame retardant, which reduced the peak heat release rate (PHRR) of EP by 72.9% . Liu et al prepared the complexes derived from sodium alginate with Fe 3+ and Ni 2+ , respectively, and the results showed that the total smoke production (TSP) of the modified EP was reduced by 42.2 and 56.3%, respectively. , Nabipour et al introduced guanazole–metal complexes into cotton; the modified cotton exhibited flame retardant and antibacterial properties . Yu et al prepared fire-preventing triple-network hydrogels with poly­( N -isopropylacrylamide)/sodium alginate/poly­(vinyl alcohol) and used them to improve the flame retardancy and antibacterial properties of cotton fabrics .…”
Section: Introductionmentioning
confidence: 99%